2004
DOI: 10.1029/2004jb002969
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale elongated gas blowouts along the U.S. Atlantic margin

Abstract: [1] In May 2000 we surveyed a series of en echelon, asymmetric depressions along the outer shelf off Virginia and North Carolina using high-resolution chirp and side-scan sonar. The features, which are elongated parallel to the shelf edge and have steep landward walls, are $4 km long, 1 km wide, and up to 50 m deep. On the basis of internal stratal geometry interpreted from chirp profiles, the depressions do not appear to result from simple, down-to-the-east, normal displacement along deep-seated faults or str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 28 publications
(48 reference statements)
3
40
1
1
Order By: Relevance
“…Such expulsion may also have a thermogenic origin at depth (Hill et al, 2004;Newman et al, 2008;Brothers et al, 2014). However, the geochemical analyses presented here yield carbonate δ 13 C values < −40h.…”
Section: Formation Model and Paleoenvironmentmentioning
confidence: 73%
See 1 more Smart Citation
“…Such expulsion may also have a thermogenic origin at depth (Hill et al, 2004;Newman et al, 2008;Brothers et al, 2014). However, the geochemical analyses presented here yield carbonate δ 13 C values < −40h.…”
Section: Formation Model and Paleoenvironmentmentioning
confidence: 73%
“…This agrees with earlier work by Newman et al (2008) that demonstrated the microbial origin of pore fluid DIC δ 13 C values along the US mid-Atlantic shelf break. Hill et al (2004) argued that microbial gas flowing updip from dissociating gas hydrates is responsible for the distribution of gas blowouts in the region, and Skarke et al (2014) make the same argument for the distribution of hundreds of seeps on the continental slope updip of the present-day hydrate stability limit, particularly on the mid-Atlantic part of the margin. Recent multi-channel seismic profiles on the upper continental slope below the Baltimore Canyon seep field do not reveal clear evidence for strata that could be laterally channeling gas updip into the seeps (Ruppel et al, 2015b), but these observations are equivocal.…”
Section: Formation Model and Paleoenvironmentmentioning
confidence: 99%
“…Seismic studies often show "wipeout zones" where the bubble zone beneath the hydrate stability zone is missing, and all of the layered structure of the sediment column within the stability zone is smoothed out. These are interpreted to be areas where gas has broken through the structure of the sediment to escape to the ocean (Riedel et al, 2002;Wood et al, 2002;Hill et al, 2004). Bubbles associated with seismic wipeout zones are observed within the depth range which should be within the hydrate stability zone, assuming that the temperature of the sediment column is the steady-state expression of the local average geothermal gradient (Gorman et al, 2002).…”
Section: Gas Migrationmentioning
confidence: 99%
“…The sediment surface of the world's ocean has holes in it called pockmarks (Hovland and Judd, 1988;Hill et al, 2004), interpreted to be the result of catastrophic or continuous escape of gas to the ocean. Pockmarks off Norway are accompanied by authigenic carbonate deposits associated with anerobic oxidation of methane (Hovland et al, 2005).…”
Section: Pockmarksmentioning
confidence: 99%
“…Outer shelf cracks and elongated depression features were first discovered along a 40-km-long section of the U.S. Atlantic margin (Driscoll et al 2000;Hill et al 2004). The individual cracks are several km long, 1 km wide and up to 50 m deep.…”
Section: Introductionmentioning
confidence: 99%